2005
DOI: 10.1007/bf03018586
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral near-infrared spectroscopy in adult heart surgery: systematic review of its clinical efficacy

Abstract: P Pu ur rp po os se e: : This systematic review is aimed at answering the following questions: 1) Is near-infrared spectroscopy (NIRS) clinically effective in detecting cerebral desaturation during heart surgery? 2) Are these results based on studies with solid methodology?S So ou ur rc ce es s: : MEDLINE, internet, and hand searches up to February 2004 for English and French papers on NIRS.P Pr ri in nc ci ip pa al l f fi in nd di in ng gs s: : Forty-eight papers were retrieved, with a total of 5,931 cardiac … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
78
0
13

Year Published

2010
2010
2018
2018

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 130 publications
(93 citation statements)
references
References 55 publications
(49 reference statements)
2
78
0
13
Order By: Relevance
“…16 NIRS is gradually starting to be used to assess cerebral oxygenation in other diseases. Frish et al used NIRS to assess the effectiveness of resuscitation in five patients on whom they performed cardiopulmonary resuscitation and reported that NIRS can be beneficial in evaluating cerebral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…16 NIRS is gradually starting to be used to assess cerebral oxygenation in other diseases. Frish et al used NIRS to assess the effectiveness of resuscitation in five patients on whom they performed cardiopulmonary resuscitation and reported that NIRS can be beneficial in evaluating cerebral circulation.…”
Section: Discussionmentioning
confidence: 99%
“…Our goal is to maintain a cardiac index of 2.4L/min/m 2 although it is not uncommon to fall just short of that mark. We do, however, utilize near-infrared spectroscopy or NIRS (Fore-Sight Cerebral Oximeter, Cas Medical Systems, Branford, CT) to monitor brain desaturation episodes routinely and use that information to help determine the adequacy of pump flow [29].…”
Section: M-cpb Techniquesmentioning
confidence: 99%
“…Mostly rSO 2 has been the parameter of choice, and studies have defined a clear cut-off value: a drop of more than 20 per cent in this parameter [97] has been shown to be a useful basis on which to devise an algorithm to counteract the risk of cerebrovascular injury [98]. A number of excellent reviews have discussed the validity of intraoperative monitoring using OI, with somewhat diverging conclusions ranging from modest to clear evidence that it is useful [99][100][101]. Although the superiority of OI compared with 'established' electrophysiological or TCD monitoring is hotly debated-e.g.…”
Section: Prevention Of Stroke In High-risk Populations (A) Intra-opermentioning
confidence: 99%